2018
DOI: 10.1039/c7dt03400h
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective alpha-cleavage of the human prion protein significantly impacts Cu(ii) coordination at its His111 site

Abstract: The cellular prion protein (PrPC) is a copper binding protein that undergoes post-translational modifications, such as endoproteolytic alpha cleavage, which occurs in the vicinity of the His111 Cu binding site. Alpha cleavage processing of PrPC is considered to be neuroprotective since the cleavage site is located in a region that is key to the conversion of PrPC into the infectious scrapie isoform (PrPSc), yielding a membrane bound C1 fragment of PrPC that still contains His111. In this work, we use hPrP(111-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Specifically, the imidazole ring of histidine is significantly related to the interaction between PrP C and copper [28,29]. In a recent study, neuroprotective αcleavage event of PrP C significantly influences on Cu (II) coordination at its His111 site [30].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the imidazole ring of histidine is significantly related to the interaction between PrP C and copper [28,29]. In a recent study, neuroprotective αcleavage event of PrP C significantly influences on Cu (II) coordination at its His111 site [30].…”
Section: Discussionmentioning
confidence: 99%
“…By using different spectroscopic techniques, studies have also focused on the Cu(II) coordination to the C1 fragment, which includes the His111, as result of the neuroprotective alpha-cleavage [109]. By using the PrP(111–115) fragment as a model system, it was shown that the His111 and the free NH 2 group act as an anchoring site for Cu 2+ , resulting in different coordination modes, depending on proton and copper concentrations ([109] and reviewed in [110]).…”
Section: Copper-binding Modelsmentioning
confidence: 99%
“…The released N1 fragment may still contain the OR region and the His96 site; however, the His111 site may be significantly disturbed, as the cleavage occurs between residues that participate in Cu 2+ coordination, leaving a His111 with a free NH 2 terminal group at the membrane bound C1 fragment. A recent spectroscopic study determined the impact of α-cleavage processing on Cu 2+ binding to His111, using a model peptide for the C1 fragment [116]. Indeed, in this fragment His111 and the free NH 2 terminal group act as the main anchoring sites for Cu 2+ , resulting in coordination modes that are highly dependent on proton and copper concentrations, and are quite different from those characterized for the intact His111 site in the full protein (Figure 3).…”
Section: Copper Bindingmentioning
confidence: 99%